Work Stress, Burnout Levels, and Affecting Factors in Nurses in Neonatal Intensive Care Units - Fatma Bozdağ; Duygu Kemer; Hülya Karataş; Mehmet Emin Düken (Galenos Publishing House, 2024)
Objective: The aim of this study was to investigate the work stress and burnout levels of neonatal intensive care nurses and the factors affecting them. Method: This descriptive study was conducted with 270 (73%) of 372 neonatal intensive care nurses who were working in neonatal intensive care units in Şanlıurfa province. Data were collected electronically with Google Form using the descriptive characteristics form, Maslach burnout inventory, and general work stress scale. The linear regression (enter) method was used to evaluate the data. Results: It was found that nurses working in the neonatal intensive care unit experienced work stress slightly above medium level and emotional burnout at a level close to medium. It was also found that the sense of personal accomplishment was low along with depersonalization. A strong positive correlation was found between the scores of nurses on the general work stress scale and their scores on the Maslach burnout inventory subscales. It was also found that emotional burnout, depersonalisation and sense of personal accomplishment experienced by nurses explained 70.3% of their general work stress. Conclusion: Burnout and work stress levels of neonatal intensive care nurses were affected by many factors such as gender, marital status, previous education, shift system, and length of service. It is recommended that regular meetings should be held with nurses, prioritised problems should be considered and psychological support should be provided to nurses working in specialized units such as neonatal intensive care.